(untitled) - Dorin, Patrick C. (Seattle, 1969)
Well-done pictorial history of the railroads that served the great iron ore mines of Lake Superior, the Menominee and the Cuyuna Ranges: the Duluth Missabe and Iron Range Railway, the Lake Superior and Ishpeming Railroad, the Great Northern, the Chicago & North Western, the Milwaukee Road, the Soo Line, Canadian National, Reserve Mining Co., Erie Mining Co., the Algoma Central, and the Northern Pacific. There are also pictures of the port facilities and some of the freighters. With maps and gradient profiles. 144 pages with index.
Keywords: Công nghiệp đường sắt,Railroads, Industrial; Superior, Lake,Superior, Lake